The Effect of Cooperative Learning Model Type Tgt Assisted by PPT Integrated Quizizz Paper Mode on Mastery of Physics Concepts in Senior High School - Rahmawati, Novi; Mahardika, I Ketut; -, Maryani (International Journal of Education, Information Technology, and Others, 2025)
In learning physics, mastery of concepts is a basic element that must be mastered by students. This is because physics emphasizes understanding natural phenomena and abstract natural principles, so logical thinking is needed to understand this in depth. Without good concept mastery, students will experience obstacles to solving problems, understanding physical phenomena, and applying them in the context of everyday life. However, current learning has not been able to have a meaningful impact on students' concept mastery, especially in physics, which is considered an abstract subject. Therefore, innovations are needed related to learning models and media, one of which is the TGT type cooperative learning model assisted by PPT integrated Quizizz Paper Mode. The approach used in this research is quantitative. The method used is an experiment with a type of quasi-experimental design, namely a non-equivalent control group design. This research was conducted at SMAN Arjasa Jember in early 2025. Sample selection using nonprobability sampling type purposive sampling and obtained class XI-1 as the experimental class and class XI-2 as the control class. Before being given treatment, both classes were given a pretest to determine students' initial concept mastery. After the treatment, both classes were given a posttest and obtained a significance value smaller than 0.05, which showed a difference in concept mastery between the experimental and control classes. Thus, it can be concluded that the TGT type cooperative learning model assisted by PPT integrated Quizizz Paper Mode has a significant effect on the mastery of physics concepts in high school.